Degradation of [D-Leu]-Microcystin-LR by solar heterogeneous photocatalysis (TiO2) - Domingues Vilela, Willian Fernando; Minillo, Alessandro [UNESP]; Rocha, Odete; Vieira, Eny Maria; Azevedo, Eduardo Bessa (Pergamon-Elsevier B.V. Ltd, 2012)
The present study investigates the use of solar heterogeneous photocatalyis (TiO2) for the destruction of [D-Leu]-Microcystin-LR, powerful toxin of widespread occurrence within cyanobacteria blooms. We extracted [D-Leu]-Microcystin-LR from a culture of Microcystis spp. and used a flat plate glass reactor coated with TiO2 (Degussa, P25) for the degradation studies. The irradiance was measured during the experiments with the aid of a spectroradiometer. After the degradation experiments, toxin concentrations were determined by HPLC and mineralization by TOC analyses. Acute and chronic toxicities were, quantified using mice and phosphatase inhibition in vitro assays, respectively. According to the performed experiments, 150 min were necessary to reduce the toxin concentration to the WHO's guideline for drinking water (from 10 to 1 mu g L-1) and to mineralize 90% of the initial carbon content. Another important finding is that solar heterogeneous photocatalysis was a destructive process indeed, not only for the toxin, but also for the other extract components and degradation products generated. Moreover, toxicity tests using mice have shown that the acute effect caused by the initial sample was removed. However, tests using the phosphatase enzyme indicated that it may be formed products capable of inducing chronic effects on mammals. The performed experiments indicate the feasibility of using solar heterogeneous photocatalysis for treating contaminated water with [D-Leu]-Microcystin-LR, not only due to its destruction, but also to the significant removal of organic matter and acute toxicity that can be achieved. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: [D-Leu]-Microcystin-LR; Microcystin; Solar photocatalysis; TiO2; Toxicity